Hermann’s Brain Dominance Instrument Psychometric Characteristics and its Use to Reveal Patterns of Brain Dominance in Jordanian University Students - Nofal, Mohammad; Abu Awwad, Ferial (Jordan Journal of Educational Sciences, 2007)
This study aims at investigating brain dominance Instrument Psychometric Characteristics and using it in revealing patterns of Brain Dominance in Jordanian undergraduate university students, The two researchers developed Ned Hermann Brain Dominance Instrument (HBDI). Development went through several steps in which the instrument validity and reliability was examined. The study instrument was applied to the sample which consisted of 500 subjects. The findings of the study revealed the commonness of the brain dominance pattern associated with the lower left brain part B, followed by the brain dominance pattern associated with the upper left brain part A; the brain dominance pattern connected with the left brain hemisphere was the commonest; and the brain dominance pattern joined with the right brain hemisphere was less common. However, the study variables had a significant effect on some brain dominance patterns at level (a≤0.05). The study ended with some comments.